MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS, KOLABORASI, DANKOMUNIKASI PADA PENDIDIKAN PANCASILA MENGGUNAKAN MODELPEMBELAJARAN PCT KELAS V SDN MAWAR 7 BANJARMASIN - Misbahul Munir; Zain Ahmad Fauzi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to improve students critical thinking, collaboration, and communication skills in Pancasila Education through the PCT learning model. This Classroom Action Research employed qualitative and quantitative approaches involving 25 fifth-grade students of SDN Mawar 7 Banjarmasin during the 2025/2026 academic year. Data were collected through observation and learning outcome tests and analyzed descriptively using percentage analysis. The results showed consistent improvement in all observed aspects. Teacher activity increased from 94% to 100%, student activity from 48% to 92%, critical thinking skills from 40% to 92%, collaboration skills from 68% to 100%, communication skills from 44% to 92%, and learning outcomes from 32% to 96% classical mastery. The findings indicate that the PCT learning model effectively improves learning processes and students' 21st-century skills in elementary Pancasila Education.